Role of MurT C-Terminal Domain in the Amidation of Staphylococcus aureus Peptidoglycan - Gonçalves, Barbara V. (2020)
Fundacao para a Ciencia e a Tecnologia (FCT) through grants PTDC/FIS-NAN/ 0117/2014 and PTDC/BIA-MIC/31645/2017. project UID/Multi/04378/2019 (Unidade de Ciencias Biomoleculares Aplicadas-UCIBIO), funded by FCT/MCTES; project LISBOA-01-0145-FEDER-007660 (Microbiologia Molecular, Estrutural e Celular), funded by FEDER through COMPETE2020-Programa Operacional Competitividade e Internacionalizacao (POCI); national funds through FCT; by project ONEIDA (LISBOA-01-0145-FEDER-016417), cofunded by FEEI (Fundos Europeus Estruturais e de Investimento) from the Programa Operacional Regional Lisboa 2020; and by national funds from FCT. Funding was also provided by European Society of Clinical Microbiology and Infectious Diseases research grant 2015, awarded to R.G.S. B.V.G., T.A.F., and I.R.G. were supported by fellowships SFRH/BD/131623/2017 respectively. J.S.D. acknowledges the National NMR Network (PTNMR) and Infrastructure Project ROTEIRO/0031/2013-PINFRA/22161/2016 (cofinanced by FEDER through COMPETE 2020, POCI, PORL, and FCT through PIDDAC).